Prediction of inflammation in hemodialysis patients using neural network analysis - Hadi H. Hadi; Hawraa H. Al-Mayali; Habiba K. Abdalsada; Shatha R. Moustafa; Abbas F. Almulla; Hussein K. Al-Hakeim (Инфекция и иммунитет, 2023)
Background. Numerous hemodialysis patients (HD) suffer from severe, life-threatening inflammation that must be treated to prevent further complications. Early diagnosis of inflammation in HD is highly needed. The present study used matrix metalloproteinase-1 (MMP3) and tissue inhibitor of metalloproteinases-1 (TIMP1) to differentiate between patients with/without inflammation using the neural network analysis (NN).